Pengembangan Media Pembelajaran Google Sites Terintegrasi Augmented Reality Pada Topik Bentuk Molekul - Hidayati, Ririn Eva (Balai Diklat Keagamaan Surabaya, 2023)
The purpose of this research is to make a product in the form of an integrated Augmented Reality Google Sites learning tool that is valid, effective, and practical. This type of research is classified as research and development using the Thiagarajan 4D development model and involving 30 class X-E MAN 1 Kota Malang students. The instruments used in this study incorporate validation sheets, test questions, and questionnaires. The evidence was scrutinized by applying Aiken's V and descriptive statistics. The data obtained in the study show that: (1) the resulting product is included in the very valid category with an average percentage of 91% (2) the mean value of the respondent's test score after utilizing the media is 70 which designates that the media is categorized as effective, and (3) the mean value retort to the media is 88% which indicates that the media is excellent and very experiential. These products are suitable for application and can prop up the proficiency of technology-based concepts, mainly on the topic of molecular shapes.